2007
DOI: 10.3233/jad-2007-12210
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid and N-acetyl Cysteine Decrease Mitochondrial-Related Oxidative Stress in Alzheimer Disease Patient Fibroblasts

Abstract: Abstract. In this study, we evaluated the effect of lipoic acid (LA) and N -acetyl cysteine (NAC) on oxidative [4-hydroxy-2-nonenal, N ε -(carboxymethyl)lysine and heme oxygenase-1] and apoptotic (caspase 9 and Bax) markers in fibroblasts from patients with Alzheimer disease (AD) and age-matched and young controls. AD fibroblasts showed the highest levels of oxidative stress, and the antioxidants, lipoic acid (1 mM) and/or N -acetyl cysteine (100 µM) exerted a protective effect as evidenced by decreases in oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 79 publications
3
97
1
1
Order By: Relevance
“…Defects in LA biosynthesis in human subjects can lead to the development of mitochondrial diseases, as has been shown in children with a mutation of NFU1, which is necessary for maturation of proteins such as succinate dehydrogenase or lipoic synthase (215). An in vitro study has shown that LA exerts a protective effect in fibroblasts obtained from patients with AD, as evidenced by decreases in oxidative stress and apoptotic markers, and this action is enhanced when LA is combined with NAC (206).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 92%
“…Defects in LA biosynthesis in human subjects can lead to the development of mitochondrial diseases, as has been shown in children with a mutation of NFU1, which is necessary for maturation of proteins such as succinate dehydrogenase or lipoic synthase (215). An in vitro study has shown that LA exerts a protective effect in fibroblasts obtained from patients with AD, as evidenced by decreases in oxidative stress and apoptotic markers, and this action is enhanced when LA is combined with NAC (206).…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 92%
“…46 N-acetylcysteine has the ability to improve markers of oxidative stress in cell lines derived from patients with mitochondrial respiratory chain disorders or Huntington disease and in a Huntington disease animal model. [47][48][49] There have been case reports in which NAC was used to treat primary mitochondrial disorders. For example, 2 mitochondrial disease patients who had significant liver dysfunction, including elevated transaminases and coagulation abnormalities, showed normalization of laboratory studies within 3 to 7 days after starting NAC.…”
Section: Parkinson Diseasementioning
confidence: 99%
“…It is reasonable to suspect that an age-related decline in brain glutathione and Nrf2 could exacerbate their progression. Indeed, NAC has shown efficacy in rodent models of these disorders (Offen et al 1996;Martinez 2000;Chen et al 2007;Clark et al 2010;Berman et al 2011;Martinez-Banaclocha 2012;Smeyne and Smeyne 2013;Moreira et al 2007;Huang et al 2010;Pocernich and Butterfield 2012;Hsiao et al 2012;Farr et al 2003). NAC is also beneficial in a mouse model of ALS (Andreassen et al 2000).…”
Section: Supplemental Nac In Aging Humans and Rodents Provides Versatmentioning
confidence: 99%